NON VIOLENCE I SOLIDARNOŚĆ JAKO CHRZEŚCIJAŃSKA ODPOWIEDŹ NA NIENAWIŚĆ - Drożdź, Alojzy (Studia Pastoralne, 2023)
Man is a rational and free being. He can choose good or evil. Evil also has various varieties. One can not accept the enlightenment belief that “selfishness will result in altruism”. Selfishness – will always be selfish. Christian morality manifests itself in the ethics of blessing. Hatred, on the other hand, is closely connected with aversion to others, with a bad attitude, disrespect for them, and finally with hostility and hatred. Today hostility and hatred are sometimes narrowed down to the “hate speech”. Already Socrates, Plato, Aristotle, Seneca, or Saint Augustine tried to show the main determinants of hatred. It is based on seven major defects. It is also known that hatred can take on various shapes (odium inimititiae, odium abominantiae). The main manifestation of hatred is all kinds of war. It should be reminded, that St. John Paul II repeatedly, especially during pilgrimages to Poland, referred to the evangelical principle that evil can only be won with good. This principle, in turn, underlies the foundations of the ethics of solidarity with the suffering and persecuted. The ethics of solidarity is inseparable from real human promotion, from eliminating violence in the modern world.